Cutaneous granular cell tumor clinically mimicking ectopic breast diagnosed on fine needle aspiration cytology. Issue 4 (18th December 2018) - Keloth, Thara; Sreerekha, Jinkala; Gochhait, Debasis; Kekade, Shailesh; Siddaraju, Neelaiah; Sistla, Sarath
Abstract: Granular cell tumor (GCT) is a rare benign neoplasm of Schwannian origin which accounts of 0.5% of soft tissue tumors. Although the most common site for GCT is tongue, it can occur at any site. GCT presenting as cutaneous nodule is rare, however cases have been reported in literature. We hereby document a case of 30 year female with a hyper‐pigmented cutaneous nodule of anterior chest wall on the milk‐line mimicking as an ectopic breast, diagnosed as GCT on fine needle aspiration cytology. We also add a note on the differential diagnoses of GCT with differentiating cytological features to emphasize on the correct diagnosis of GCT pre‐operatively.